Endothelial Function and Aminothiol Biomarkers of Oxidative Stress in Healthy Adults - Ashfaq, Salman; Abramson, Jerome L.; Jones, Dean P.; Rhodes, Steven D.; Weintraub, William S.; Hooper, W Craig; Vaccarino, Viola; Alexander, R Wayne; Harrison, David G.; Quyyumi, Arshed A. (Hypertension (Dallas, Tex. 1979), 2008)
Endothelial dysfunction is known to precede the development of atherosclerosis and results primarily from increased oxidative degradation of NO. We hypothesized that assessment of oxidative stress in the bloodstream will reliably predict endothelial function in healthy adults. A total of 124 healthy nonsmokers had endothelial function assessed using ultrasound measurement of brachial artery flow-mediated vasodilation. Plasma oxidative stress was estimated by measuring the levels of the reduced and oxidized forms of thiols, including glutathione (reduced glutathione and oxidized glutathione) and cysteine (cysteine and cystine), respectively, and the mixed disulfide. Among the traditional risk factors, there were significant and independent correlations between flow-mediated vasodilation and high-density lipoprotein level, body mass index, gender, and the Framingham risk score. Among the thiol markers, plasma cystine (r=−0.23; P=0.009) and the mixed disulfide (r=−0.23; P=0.01) levels correlated with endothelium-dependent but not endothelium-independent vasodilation, even after adjusting for the Framingham risk score and high-sensitivity C-reactive protein level. A higher level of oxidized metabolites was associated with worse endothelial function. In conclusion, the oxidative stress markers, cystine, and the mixed disulfide are independent predictors of endothelial function. These markers, in combination with the Framingham risk score, may help in the early identification of asymptomatic subjects with endothelial dysfunction who are at potentially increased risk for future atherosclerotic disease progression.